ALIGNING THE TOEFL PREDICTION SCORES TO THE COMMON EUROPEAN FRAMEWORK OF REFERENCE FOR LANGUAGES (CEFR) LEVEL - Sri Supeni; Anna Fauziah (Journal of English Language and Literature (JELL), 2020)
TOEFL as a kind of English test is used to measure students’ language proficiency. Binawan University applies TOEFL Prediction test to predict students’ English competence. The TOEFL score then is aligned and mapped to CEFR to indicate the level of language ability and qualification. This study was conducted to analyze TOEFL score of Binawan students at CEFR level. The sample was 169 students from several study programs at Binawan University. The research instrument used a package of PBT TOEFL test. Descriptive statistics was used as data analysis technique, mean and percentage. The calculation shows that the mean of the TOEFL prediction score reached by all participants is 413 and the median is 397. Based on CEFR, the students’ competence in English is in level A2 (Basic User). Individually, the number of students who is in level A1 (Basic User) is 78 or 46.2 %, level A2 (Basic User) is 35 or 20.7 %, level B1 (Independent User) is 43 or 25.4 %, level B2 (independent User) is 12 or 7.1 %, and the last is level C1 which is occupied by 1 student only that is in level C1 (0.6 %). To conclude almost 50 % of the students were at low level or A2 (Basic User) at CEFR.